Seed morphological traits and their implication in the ex situ conservation of woody species in Tumbesian dry forests [Rasgos morfológicos de semillas y su implicación en la conservación ex situde especies leñosas en los bosques secos Tumbesinos] - Romero Saritama, J. (2016)
There is currently a great interest in discovering and studying functional traits in plants that help us predict certain behaviors and ecological interactions of species to environmental or anthropological changes in ecosystems. Morphological traits identified in the seeds are involved in processes during the life cycle of plants. However, they have not been well studied functionally in different habitats, especially in tropical dry areas, where there is great diversity of species at high risk of threat. The Tumbesian Dry Forests shared between northwestern Ecuador and northwestern Peru, they have been regarded as hotspots for their high diversity and endemism. However, they are very threatened and some forest species have already been included in red lists with some degree of threat because of the major environmental problems affecting these forests. For this reason, it is urgent to generate research and information to permit conservation of forest genetic resources. One of the most practical and immediate alternative is the collection and ex situ seed storage. Unfortunately, in tropical dry habitats, ecology, physiology and morphology of seeds that allows efficiently determine the storage type is unknown, limiting the effective process for ex situ long-term conservation of the species. Linking information about morphological seed traits we could help predict the best way to collect and conserve forest species. This article analyzes and incorporates information about morphological seeds traits of woody species that have been little or nothing studied from a functional point on tumbesian dry forests, and analyzes how information morphological seeds traits could serve as a tool to optimize and accelerate the process of ex situ wildlife conservation highly threatened habitats.